The history of neuromyelitis optica. Part 2: 'Spinal amaurosis', or how it all began - Jarius, Sven; Wildemann, Brigitte (Journal of neuroinflammation, 2019)
Neuromyelitis optica (NMO) was long considered a clinical variant of multiple sclerosis (MS). However, the discovery of a novel and pathogenic anti-astrocytic serum autoantibody targeting aquaporin-4 (termed NMO-IgG or AQP4-Ab), the most abundant water channel protein in the central nervous system, led to the recognition of NMO as a distinct disease entity in its own right and generated strong and persisting interest in the condition. NMO is now studied as a prototypic autoimmune disorder, which differs from MS in terms of immunopathogenesis, clinicoradiological presentation, optimum treatment, and prognosis. While the history of classic MS has been extensively studied, relatively little is known about the history of NMO. In Part 1 of this series we focused on the late 19th century, when the term 'neuromyelitis optica' was first coined, traced the term's origins and followed its meandering evolution throughout the 20th and into the 21st century. Here, in Part 2, we demonstrate that the peculiar concurrence of acute optic nerve and spinal cord affliction characteristic for NMO caught the attention of physicians much earlier than previously thought by re-presenting a number of very early cases of possible NMO that date back to the late 18th and early 19th century. In addition, we comprehensively discuss the pioneering concept of 'spinal amaurosis', which was introduced into the medical literature by ophthalmologists in the first half of the 19th century.
Gesehen am 24.02.2020